DMFT of the First Permanent Molars, dmft and Related Factors among All First-Grade Primary School Students in Rafsanjan Urban Area - Nazanin Kamiab; Yasaman Mohammadi Kamalabadi; Mahmood Sheikh Fathollahi (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: Dental caries is the most common chronic childhood disorders throughout the world. The dmft (decayed, missing, and filled primary teeth) and DMFT (decayed, missing, and filled permanent teeth) are some of the most important epidemiological indices in dentistry. Evaluation of these two indicators in the population can help in future planning of healthcare programs to improve oral health status. Purpose: The aim of this study was to evaluate these indicators and the related factors in first-grade primary school students in Rafsanjan urban area to determine their present status, which might be helpful for future health care planning. Materials and Method: In this cross-sectional study, DMFT index of first permanent molar and dmft were evaluated by census method on 2031 first-grade primary school students in Rafsanjan urban area in 2018 (May-June). Dental examination was done using a mirror and probe under natural light according to World Health Organization criteria. The data were then analyzed using independent two-sample t-test, one-way ANOVA, Tukey's multiple comparisons test, Kolmogorov-Smirnov nonparametric test and Leven's test in SPSS version 21 software. Results: The mean and standard deviation of dmft index and DMFT index of first permanent molar were 6.37 ± 3.40 and 0.30 ± 0.72, respectively. The proportion of caries free students was 4.1%. A significant association was found between the values of these indices and school type, the level of education of parents, parental occupation, family size, and frequency of brushing and the use of floss (p < 0.05). However, there was no significant association between these two indices with gender (p= 0.347 and p= 0.593, respectively). Conclusion: The results of this study showed high prevalence of caries in first-grade primary school students in Rafsanjan. Therefore, to improve this situation, more attention is needed for proper oral health program planning and education of families concerning oral hygiene and dental preventive measures.